Nilai Tarbawi Q.S. Al-‘Alaq Ayat 1–5 dalam Pendidikan Literasi Islam - Ayu Lavenia, Bunga; Mirza, Iskandar (Jurnal Penelitian Tarbawi: Pendidikan Islam dan Isu-Isu Sosial, 2026)
Jurnal This article aims to analyze the tarbawi values ​​contained in Q.S. Al-'Alaq verses 1–5 and their relevance for strengthening Qur'anic literacy education in the context of contemporary Islamic education. The main problem raised is the tendency for literacy practices in Islamic education to still be technical and not yet optimally integrated with the values ​​of monotheism, scientific ethics and humanitarian development. This research uses a qualitative approach with a type of library research through an approach to tarbawi interpretation and Islamic education. The research results show that Q.S. Al-'Alaq verses 1–5 contain literacy values ​​based on monotheism, development of intellectual and human potential, as well as scientific ethics and critical literacy. These values ​​are relevant to answering the challenges of literacy education in the contemporary era which is characterized by massive and complex information flows. The integration of Al-Qur'an tarbawi values ​​in literacy education is expected to be able to form students who are not only academically competent, but also have faith, morals and social responsibility.